Draft Annual Plan 1990-91 Volume-II(B) Government of Arunachal Pradesh - Planning Commission (Planning Commission, 1990)
The North Eastern Region is end owned with large amount/ of Hydroelectric potential as assessed by the Central Electricity Authority. The detailed power studies are required to be conducted and whole integrated plans prepared to tap the huge hydro-electric potential. The accelerated hydel development is also extremely important from various national considerations, such as environmental hazards, conservation of deplete able fossil fuels, reduction in overall electricity generation costs. In view of this, there is a need to take firm action for taking up the investigation of various hydro-electric projects as well tapping of small and big hyd.ro electric projects in Arunachal Pradesh. Arunachal Pradesh have already, though completed 24 Micro Hydel Schemes; in isolated manner, which are too insufficient to meet the growing demand. The demand is being supplemented by the diesel generation for which efforts are being tried to reduce gradually by import of power from Assam. During 8th Five Year Plan, more emphasis is given from hydel power generation and its transmission. Arunachal Pradesh is also having sufficient natural gas yield in the Eastern rector. Installing, a gas turbine is considered a viable project for enhancing the power generation and provision is being proposed in the Annual Plan.
Government of Arunachal Pradesh
Government of Arunachal Pradesh Planning and Development Department Itanagar
Keywords: Power; Housing; Urban Development; Water Supply (Admin centers); Medium Irrigation and Flood control; Hydel Generation; Diesel Generation; Transmission & Distribution; Rural Electrification; Border villages electrifications under State Plan; Survey & Investigation under NEC; Establishment